Long COVID: A New Challenge for Prevention of Obesity in Women. Issue 1 (January 2023) - Mattioli, Anna Vittoria; Coppi, Francesca; Nasi, Milena; Pinti, Marcello; Gallina, Sabina
The long COVID affects individuals that do not recover for several weeks or months following the onset of symptoms of COVID-19. Obesity could play a role in the long COVID syndrome. During the pandemic, various factors contributed greatly to aggravating obesity in women leading to a pro-inflammatory and prothrombotic status. The present commentary explores the relationship between long COVID and obesity in women.